The Impact of COVID-19 on Plastic Waste Management in South Asia : Challenges and Policy Recommendations - World Bank (World Bank, Washington, DC, 2021)
This report is part of a larger series of stocktaking and analytical products on plastic pollution in South Asia. It supports the Bank’s commitment to work with countries of South Asia to pursue and scale-up policies and programs that help them move toward a circular plastic economy and, in partnership with civil society and the private sector, harnesses the power of innovation to bring viable and sustainable solutions for plastic waste reduction and management across the region. This report is supported through the South Asia Water Initiative (SAWI), a multi-donor trust fund administered by the World Bank and designed to build a shared understanding of transboundary river pollution flows in South Asia, especially plastics pollution.